Health Nutrition Education and Strengthening Indonesian Culture Among Indonesian Migrant Workers Children in Malaysia - Rahmaddiansyah, Refa; Azizah, Aghasi Yanda Wafa; Abdurrahman, Adisa Muhammad; Muftiana, Sintya Nur; Haq, Addienul; Riswanti, Laila Wulan; Jalilah, Thurfah Hashifah; Masthurina, Ulfa; Hrp, Maritza Briliani Namora; Tambunan, Mega Intan; Pelani, Achmad Aziz; Noviar, Tita Falisha; Abdurrahman, Thariq; Azizah, Siti Nur (ISEI Cabang Pekanbaru, Koordinator Provinsi Riau, 2024)
In September 2015, the United Nations General Assembly adopted the 2030 Agenda for Sustainable Development, featuring 17 Sustainable Development Goals (SDGs) that address global issues like poverty, inequality, and education. This agenda highlights the importance of inclusivity, particularly regarding the vulnerabilities of migrant populations. Indonesian migrant children in Malaysia face significant barriers to education and health due to socio-economic factors and cultural challenges, often lacking access to formal education and relying on alternative learning centers like Sanggar Bimbingan. To tackle these issues, the